Lessons for pumped hydro energy storage systems uptake - Domfeh, M. K.; Diawuo, F. A.; Akpoti, Komlavi; Antwi, E. O.; Kabo-bah, A. T. (Elsevier, 2023)
Pumped hydro energy storage (PHES) has for years been touted as a suitable alternative for balancing the mismatch between demand and supply of electricity. As the world transits from a fossil fuel-based electricity sector to a renewable energy-based one, PHES is also continuously being used to resolve challenges regarding variable or intermittent sources of energy. This chapter presents lessons from countless literature and studies on the global development and market environment of PHES. The study reveals that critical factors such as investing in public-private research, development and deployment, instituting regulatory frameworks that stimulate innovative operation of PHES, increasing digital operation of PHES systems, and retrofitting PHES facilities could foster the uptake and revolutionize the development of PHES.